Gemeinsam/Together Kognitiv beeintraechtigte Menschen in europaeischen Theatern - Theorie und Praxis/People with Learning Disabilities in European Theatres - Theory and Practice. Unter Mitarbeit von Soledad Pereyra - Hartwig, Susanne (Images of Disability. Literature, Scenic, Visual, and Virtual Arts / Imágenes de la diversidad funcional. Literatura, artes escénicas, visuales y virtuales, 2022)
Can society mitigate hermeneutical injustice towards persons with learning disabilities? How do European theatres meet this challenge? How can artists with learning disabilities «have a voice»? The present volume searches for answers to these questions in theoretical approaches and in interviews with stage directors.